Investigation on optimum blend ratio and microwave pre-treatment condition of primary and secondary sludge from sewage treatment plants (STP) to enhance biogas production in anaerobic digesters - Sivasankari R.; Kumaran P.; Normanbhay S. (IEEE Computer Society, 2023)
In this paper, findings of an investigation to determine optimum ratio of primary and secondary sludge and microwave pre-treatment of the combined sludge ratio is reported. In the first experimental works, anaerobic digestion of primary and secondary sewage sludge at ratio of 100:0, 90:10, 70:30, 50:50, 30:70, 0:100 respectively, was carried out. Results have indicated that the highest amount of biogas was generated by the 100% primary sludge. The current practice at the STP employs 70:30 sludge mix ratio. Using microwave, the 70:30 sludge mixture was subjected to pretreatment (MW) at 5 minutes and 15 minutes of continuous and intermittent irradiation prior to anaerobic digestion and compared to samples without pretreatment. The continuously MW pretreated sludge for 15 minutes generated 25% more biogas than the non-pretreated sludge. The outcome of this work suggest, pretreating 100% primary sludge with MW irradiation may prove to be an attractive option to be explored for enhancement biogas production in STP's. The excess biogas produced can be used to generate more electricity hence proving to be techno-economically viable for power production. © 2014 Asian Institute of Technology.